2018
DOI: 10.4067/s0717-65382018000200118
|View full text |Cite
|
Sign up to set email alerts
|

Las razones de por qué Chile debe detener la importación del abejorro comercial Bombus terrestris (Linnaeus) y comenzar a controlarlo

Abstract: La crisis mundial de polinización no solo es producida por la pérdida de polinizadores, sino también por su homogeneización, ambos procesos causados por el ser humano. En este documento analizamos los impactos ecológicos que justifi can la prohibición de nuevos ingresos del abejorro comercial Bombus terrestris a Chile. Esta especie es altamente invasiva y ha sido prohibida en otros países, pero en Chile se permite su ingreso desde 1997. Miles de colonias y reinas fertilizadas ingresan al país cada año y se exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…•Bees: mentioned in religious stories, Bombus dahlbomii in Mapuche culture (Preston, 2006; Smith‐Ramírez et al ., 2018).…”
Section: Overview and Value Of Ecosystem Services Provided By Social mentioning
confidence: 99%
“…•Bees: mentioned in religious stories, Bombus dahlbomii in Mapuche culture (Preston, 2006; Smith‐Ramírez et al ., 2018).…”
Section: Overview and Value Of Ecosystem Services Provided By Social mentioning
confidence: 99%
“…B. dahlbomii was a source of medicinal honey and considered a sacred being by Mapuche, one of the First Nations people of Chile [230]. Scientists have demonstrated that Introduced bumblebee species are displacing native B. dahlbomii in Chile and Argentina, colonizing natural areas in most of the southern cone of South America, and have urged authorities to ban the imports of these IA-managed pollinators [231,232]. Even though this is a concerning situation, government policy still allows the importation of buff-tailed bumblebees for IA crop pollination in Chile [231].…”
Section: Managed Pollinatorsmentioning
confidence: 99%
“…Scientists have demonstrated that Introduced bumblebee species are displacing native B. dahlbomii in Chile and Argentina, colonizing natural areas in most of the southern cone of South America, and have urged authorities to ban the imports of these IA-managed pollinators [231,232]. Even though this is a concerning situation, government policy still allows the importation of buff-tailed bumblebees for IA crop pollination in Chile [231]. In the Mediterranean region of central Chile, a bee biodiversity hotspot [65], avocado orchards have been recorded to be profusely visited by managed A. mellifera, while five native bees species have also been reported visiting this crop [233].…”
Section: Managed Pollinatorsmentioning
confidence: 99%
“…B. dahlbomii was a source of medicinal honey and considered a sacred being by Mapuche, one of the First Nations people of Chile 230 . Scientists have demonstrated that Introduced bumblebee species are displacing native B. dahlbomii in Chile and Argentina, colonizing natural areas in most of the southern cone of South America, and have urged authorities to ban the imports of these IA-managed pollinators 231,232 .…”
Section: Managed Pollinatorsmentioning
confidence: 99%
“…Even though this is a concerning situation, government policy still allows the importation of bufftailed bumblebees for IA crop pollination in Chile 231 .…”
Section: Managed Pollinatorsmentioning
confidence: 99%